Anatomical characteristics of the furcation area and root surfaces of multi-rooted teeth: Epidemiological study - Kadović, Jana; Novaković, Nada; Jovanovic, Mila D; Djordjević, Vladan; Petrović, Vanja; Stojčev Stajčić, Ljiljana; Čakić, Saša (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Knowledge of numerous variations in anatomical features of furcation area is a prerequisite for the achievement of more predictable results in the therapy of multi-rooted teeth with furcation involvement (FI). The aim of the study was to evaluate the morphological characteristics of extracted molars of adult population in Belgrade, Serbia. Methods. In total, 468 extracted first and second molars, both mandibular and maxillary, were measured. The values of root trunk lengths and root lengths, diameter of furcation entrances (FE), distance between the roots and depth of root concavity were analysed. Results. The maxillary first molars had significantly higher root trunk lengths values than the second molars. As for the mandibular molars, FE was smaller than 1 mm. The distance between the roots was more than 2 mm at the third level of measurement. Conclusion. The buccal FE of maxillary molars was the lowest. The root concavity of the second mandibular molars was higher from the lingual aspect.
Keywords: furcation defects; molar; odontometry; tooth root